Analisa Karakterisasi Baja Paduan As-Cast-Fe-Cr-Mn-Mo Dengan Komposisi Nikel Terhadap Sifat Mekanik Dan Struktur Mikro Hasil Uji Balistik - Harna, Daryl Deskianto (Jurnal Mesin Nusantara, 2022)
Lateritic steel is a low-nickel steel with a nickel content of 1-4.5 percent. Steel with a high nickel percentage has better qualities like high strength, corrosion resistance, and weldability. This material is commonly used in crushers and grinding machines. This material can also be utilized as an armor material. A study was undertaken to investigate the ability of laterite steel to be employed as armor material by characteristic testing (impact test and hardness test) and microstructure (metallography) of laterite steel. ASTM standards must be followed in the preparation of all samples. The impact test was performed on 9 samples from 3 specimens, with each sample being placed on an anvil and pounded with a pendulum that the average values of samples A, B, and D were 11 J, 9 J, and 12 J, respectively. The fractures were granular, indicating that the material is extremely fragile. The hardness test was then performed using the Vickers method with a 5 Kgf load. The polished sample is placed immediately on a vise, and then a diamond-shaped indenter is attached; the hardness test value is determined by the size of the trace of the indenter, with the average values of samples A, B, and D being 292.63 HVN, 310.47 HVN, and 464.87 HVN, respectively. Microstructure measurements revealed that sample A formed ferrite perlite, sample B formed lower bainite, and sample D formed martensite phase.